Estimating Crop Water Requirements to Evaluate Cropping Patterns for Agriculture on Post-Tin Mining Land - Rizki Maftukhah; Novita Dyah Pitaloka; Murtiningrum Murtiningrum; Ngadisih Ngadisih (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Utilization of degraded land, such as post-mining land, for agricultural purposes necessitates significant effort, particularly land and water management. This study focuses on estimating crop water requirements (CWR), a crucial step in evaluating suitable cropping patterns for agricultural development on post-tin mining in Bangka Island. The CWR and effective rainfall (EF) of rice, cassava, and peanuts were estimated using meteorological data between 2019 and 2023. The CWR was calculated using Penman-Monteith method, while EF was determined using the USDA SCS Method. The results indicate that average potential evapotranspiration (ETo) from 2019 to 2023 varied across years. The highest ETo values were predicted as 5.6 to 5.8 mm/day, while the lowest value was estimated at 4.3 mm/day. Rice and peanut cultivation require supplemental irrigation since EF is insufficient to meet CWR. Cassava, is more suitable, with EF generally fulfilling its CWR. This study provide useful information for developing adaptive strategies that account for the effects of climatic conditions and different cropping pattern, particularly in degraded areas. Furthermore, crop selection that is adapted to the degraded area offers a long-term solution for rehabilitating degraded areas. Keywords: Agriculture, Degraded soil, Irrigation, Yield.